Analysis of Metal Content in Rocks Using X-Ray Fluorescence (XRF) - Napitupulu, Mery; Maharani, Tiara; Walanda, Daud K.; Said, Irwan (Jurnal Akademika Kimia, 2024)
Rocks in mining have different types and levels of metal from one another. This study aims to determine the levels of metals present in rocks found in illegal mining areas in the Dongi-Dongi region. The parameters tested are the type of metal contained in rocks from unlawful mining in the Dongi-Dongi area and the amount of metal content in rocks from illegal mining in the Dongi-Dongi area. The results showed that the metals contained in the five rock samples from gold mining in Dongi - Dongi were, respectively, iron (Fe), potassium (K), silicon (Si), calcium (Ca), titanium (Ti), arsenic (Ar), zirconium (Zr), manganese (Mn), rubidium (Rb), niobium (Nb), molybdenum (Mo), indium (In), strontium (Sr), tin II (Sn), and rubidium (Ru) with the highest metal percentage found in the fifth rock sample (E), namely iron (Fe) at 62.89 % and potassium (K) at 54.7 %. The high content of iron and potassium in Dongi-Dongi mining rocks has the potential to be utilized by the community, as these metals are widely used in various industrial fields.